2009
DOI: 10.1111/j.1528-1167.2008.01782.x
|View full text |Cite
|
Sign up to set email alerts
|

Aphasic or amnesic status epilepticus detected on PET but not EEG

Abstract: Summary Purpose:  To describe five patients with ictal aphasia and one patient with ictal amnesia, who had focal positron emission tomography (PET) hypermetabolism but no clear ictal activity on electroencephalography (EEG). Methods:  18F‐Fluorodeoxyglucose (FDG)–PET scans with concomitant EEG were obtained in five patients with suspected ictal aphasia or ictal amnesia without ictal activity on EEG. We reviewed medical history, EEG, imaging data, and treatment outcome. Results:  Brain magnetic resonance imagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
33
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 21 publications
5
33
0
Order By: Relevance
“…Fluctuation in the level of speech impairment and inter-ictal EEG abnormality in our patient may suggest a combination of recurrent seizure and post-ictal deficit as a mechanism for prolonged aphasia. Aphasic status epilepticus, similar to simple partial status epilepticus, may be associated with non-ictal scalp EEG, however ictal activity by intracranial EEG recording or focal hypermetabolism on PET scan has been documented in such patients [3,5,6]. A PET or SPECT scan was not performed in our patient.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Fluctuation in the level of speech impairment and inter-ictal EEG abnormality in our patient may suggest a combination of recurrent seizure and post-ictal deficit as a mechanism for prolonged aphasia. Aphasic status epilepticus, similar to simple partial status epilepticus, may be associated with non-ictal scalp EEG, however ictal activity by intracranial EEG recording or focal hypermetabolism on PET scan has been documented in such patients [3,5,6]. A PET or SPECT scan was not performed in our patient.…”
Section: Discussionmentioning
confidence: 60%
“…Aphasic seizures in almost all cases arise from the dominant hemisphere [2,3]. Epileptic focus in ictal WA has been reported in the left Journal of the Neurological Sciences 291 (2010) 98-99 temporo-parietal area, left fronto-temporal region, or basal temporal language area, based on findings of ictal EEG and/or PET scan hypermetabolism [2,3,5,6].…”
Section: Discussionmentioning
confidence: 97%
“…Ericson et al [19] found standard EEG (30 min) in aphasic status epilepticus to be sensitive in only 5/9 (56%) patients, while continuous EEG confirmed seizure activity. Dong et al [20] showed aphasic NCSE in 5 patients with (18)F-fluorodeoxyglucose positron emission tomography (FDG-PET), while EEG failed to show clear ictal activity.…”
Section: Discussionmentioning
confidence: 98%
“…In one patient in whom aphasia lasted for 1 week (initially diagnosed as post IA), intracranial electrode monitoring revealed that the patient had prolonged IA. 6 In one case series of four patients with IA, surface EEG did not reveal obvious ictal patterns and the ictal state was diagnosed by a positron emission tomography (PET) scan only. 7 Our series of patients showed that surface EEG is a good and simple way to diagnose IA.…”
Section: Discussionmentioning
confidence: 98%